2021
DOI: 10.1093/asj/sjab014
|View full text |Cite
|
Sign up to set email alerts
|

Facial Rejuvenation With Fat Grafting and Fillers

Abstract: Facial rejuvenation requires a multi-modality approach to address the sun damage, volume loss, and thinning of skin that occurs with aging. With age, the collagen fibrils that provide strength become fragmented and fibroblasts connections become weak, leading to skin laxity and loss of youthful skin. Fillers can lead to a more youthful appearance by providing volumetric support. Synthetic fillers such as hyaluronic acid products, calcium hydroxyapatite, polylactic acid, and polymethylmethacralate have bio-stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…Fat grafting and other filler injections have been widely applied in facial contouring for decades. However, the selected techniques are based on surgeons' clinical experiences, and the injection plane for filler placement varies between surgeons ( 12 ). An anatomical study of the temple ( 13 ) showed that the temporal region is comprised of two compartments, the UTC and the LTC, which are separated by the ITC.…”
Section: Disscusionmentioning
confidence: 99%
“…Fat grafting and other filler injections have been widely applied in facial contouring for decades. However, the selected techniques are based on surgeons' clinical experiences, and the injection plane for filler placement varies between surgeons ( 12 ). An anatomical study of the temple ( 13 ) showed that the temporal region is comprised of two compartments, the UTC and the LTC, which are separated by the ITC.…”
Section: Disscusionmentioning
confidence: 99%
“…Animal collagen and synthetic fillers (hyaluronic acid, calcium hydroxyapatite, polylactic acid, and polymethylmethacrylate) have volumetric and biological effects, such as effects on fibroblast production and angiogenesis. Fat grafting and autologous platelet-derived preparations are also interesting techniques for facial rejuvenation because they are autologous and have regenerative effects [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The forehead and glabella represent the most common sites for filler injections [ 11 ]. The injectables should be introduced within the loose connective tissue above the periosteum for wrinkle reduction and volume expansion.…”
Section: Aesthetic Injections and Relevant Neurovascular Structuresmentioning
confidence: 99%
“…Filler injections into the temporal area are useful to correct atrophy secondary to age-induced fat loss [ 11 ]. Medial infraorbital region injections are used to trim the tear trough, which is a deep crease between the lower eyelid and upper cheek.…”
Section: Aesthetic Injections and Relevant Neurovascular Structuresmentioning
confidence: 99%
See 1 more Smart Citation